Spruce regeneration on woody microsites in a subalpine forest in the western Carpathians - Bujoczek, Leszek; Bujoczek, Małgorzata; Banaś, Jan; Zięba, Stanisław (Silva Fennica, 2015)
The density of [L.] Karst. regeneration on different microsites, the quantity and quality of woody microsites, and seedling occurrence probability on stumps and fallen deadwood were studied in a subalpine forest that has been under protection for approximately 30â40 years (Gorce Mountains in the western Carpathians). Thirty percent of seedlings and 29% of saplings grew on stumps and fallen deadwood, while the remaining regeneration occurred on soil surface and mounds created by uprooted trees. The occurrence probability of seedlings on fallen deadwood increased with deadwood diameter and decay stage and with the volume of living trees, and decreased with increased density of living trees, sapling density, and land slope. Furthermore, seedlings were more likely to grow on stumps with a greater diameter and in plots with higher sapling density, but less likely to grow on higher stumps. Stumps and fallen deadwood covered about 4% of the forest floor, but the material that is most important for promoting regeneration (strongly decomposed logs and those of a diameter exceeding 30Â cm) took up only about 22 m ha. We have concluded that in a subalpine forest that has been protected for 30â40 years regeneration processes take place mostly on soil surface and stumps. The role of fallen deadwood increases over time as a greater number of suitable logs (in terms of size and decay stage) become available.Picea abies Picea2-1